The role of regional heterogeneity in age-related differences in functional hemispheric asymmetry : an fMRI study - Heng, Gladys Jiamin (2020)
Neuroimaging literature has documented age-related hemispheric asymmetry reduction in frontal regions during task performances. As most studies employed working memory paradigms, it is therefore less clear if this pattern of neural reorganization is constrained by working memory processes or it would also emerge in other cognitive domains which are predominantly lateralized. Using blocked functional magnetic resonance imaging (fMRI), the present study used a homophone judgment task and a line judgment task to investigate age-related differences in functional hemispheric asymmetry in language and visuospatial processing respectively. Young and older adults achieved similar task accuracy although older adults required a significantly longer time. Age-related functional hemispheric asymmetry reduction was found only in dorsal inferior frontal gyrus and was associated with better performance when the homophone condition was contrasted against fixation, and not line condition. Our data thus highlights the importance of considering regional heterogeneity of aging effects together with general age-related cognitive processes.